2021
DOI: 10.3390/ma14123268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation-Induced Crosslinking of Collagen Type I Coated Dental Titanium Implants on Osseointegration and Bone Regeneration

Abstract: This study aimed to compare two methods of crosslinking collagen type I on implanted titanium surfaces, that is, using glutaraldehyde (GA) or gamma-rays (GRs), in a beagle dog model. For in vivo experiments, implants were allocated to three groups and applied to mandibular bone defects in beagle dogs; Group SLA; non-treated Sandblasted, large grit, acid-etched (SLA) implants, Group GA; SLA implants coated with GA crosslinked collagen type I, Group GR; SLA surface implants coated with collagen type I and crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The initial electronic search yielded 10,697 references. After eliminating duplicates and irrelevant articles based on their title and abstracts, 84 articles were selected, of which, after eliminating those that did not meet inclusion criteria ( in vitro studies, systematic reviews, modified animals...), 26 full texts were selected ( Anitua, 2006 ; Germanier et al, 2006 ; Wikesjö et al, 2008a ; Wikesjö et al, 2008b ; Wikesjö et al, 2008c ; Stadlinger et al, 2008 ; Anitua et al, 2009 ; Barros et al, 2009 ; Ishibe et al, 2009 ; Yang et al, 2009 ; Lutz et al, 2010b ; Polimeni et al, 2010 ; Susin et al, 2010 ; Ramazanoglu et al, 2011 ; Stadlinger et al, 2012b ; Sverzut et al, 2012 ; Jiang et al, 2013 ; Cecconi et al, 2014 ; Korn et al, 2014 ; Kim et al, 2015 ; Yoo et al, 2015 ; Cardoso et al, 2017 ; Bae et al, 2018 ; Cho et al, 2019 ; Cho et al, 2021 ; Pang et al, 2021 ). The concordance between reviewers (N.L-V., A.L-V.) was 100% with a Cohen’s kappa index of 1 (total concordance).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial electronic search yielded 10,697 references. After eliminating duplicates and irrelevant articles based on their title and abstracts, 84 articles were selected, of which, after eliminating those that did not meet inclusion criteria ( in vitro studies, systematic reviews, modified animals...), 26 full texts were selected ( Anitua, 2006 ; Germanier et al, 2006 ; Wikesjö et al, 2008a ; Wikesjö et al, 2008b ; Wikesjö et al, 2008c ; Stadlinger et al, 2008 ; Anitua et al, 2009 ; Barros et al, 2009 ; Ishibe et al, 2009 ; Yang et al, 2009 ; Lutz et al, 2010b ; Polimeni et al, 2010 ; Susin et al, 2010 ; Ramazanoglu et al, 2011 ; Stadlinger et al, 2012b ; Sverzut et al, 2012 ; Jiang et al, 2013 ; Cecconi et al, 2014 ; Korn et al, 2014 ; Kim et al, 2015 ; Yoo et al, 2015 ; Cardoso et al, 2017 ; Bae et al, 2018 ; Cho et al, 2019 ; Cho et al, 2021 ; Pang et al, 2021 ). The concordance between reviewers (N.L-V., A.L-V.) was 100% with a Cohen’s kappa index of 1 (total concordance).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used experimental models were the dog ( Wikesjö et al, 2008a ; Wikesjö et al, 2008b ; Barros et al, 2009 ; Polimeni et al, 2010 ; Susin et al, 2010 ; Sverzut et al, 2012 ; Kim et al, 2015 ; Cho et al, 2019 ) and the pig ( Germanier et al, 2006 ; Stadlinger et al, 2008 ; Lutz et al, 2010b ; Susin et al, 2010 ; Ramazanoglu et al, 2011 ; Stadlinger et al, 2012b ; Korn et al, 2014 ; Cardoso et al, 2017 ). The jaw and tibia were the most commonly used bones for implantation and all included studies evaluated the BIC; six studies evaluated BA ( Yang et al, 2009 ; Sverzut et al, 2012 ; Yoo et al, 2015 ; Cho et al, 2019 ; Cho et al, 2021 ; Pang et al, 2021 ) and nine studies evaluated BD ( Wikesjö et al, 2008b ; Wikesjö et al, 2008c ; Stadlinger et al, 2008 ; Barros et al, 2009 ; Lutz et al, 2010b ; Polimeni et al, 2010 ; Susin et al, 2010 ; Ramazanoglu et al, 2011 ; Korn et al, 2014 ). The main characteristics of the studies are shown in the tables below ( Tables 3 – 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical functionalization of collagen throughout the extraction process removes its natural bonding; thus, biomaterials containing collagen require inter-and intra-molecular cross-linking, with the goal of improving their mechanical characteristics [149,150]. In particular, cross-linkers such as glutaraldehyde [151], gamma radiation [152], N-hydroxy succinimide [153], carbodiimide [154], formaldehyde [155], hexamethylene diisocyanate [156], sodium tripolyphosphate [157], genipin [158], transglutaminase [159], dialdehyde [160], and sugar-based [161] ones, are utilized to augment the collagen hydrogels' stability that is necessary for preventing the quick enzymatic degradation [162]. Hence, the collagen-based hydrogel is recognized as a promising choice for TE applications.…”
Section: Collagen-based Hydrogelsmentioning
confidence: 99%
“…ECM molecules such as glycosaminoglycan's (GAGs) (e.g., chondroitinsulfate (CS), heparin (Hep) and hyaluronic acid (HA)) and fibrillary glycoproteins such as collagens, fibronectins, and laminins are becoming more and more in focus for the preparation of bioactive surfaces that mimic the native ECM [7]. Hence, the deposition of ECM molecules by LbL is an excellent option to establish an ECM-like microenvironment and to improve the osseointegration of implants [8][9][10][11]. Natural polymers such as collagen, fibronectin, vitronectin, or laminin have the great advantage that they already contain specific binding motives like GFOGER, RGD, SIKVAV, or YIGSR that enable cell adhesion, proliferation, and differentiation in combination with synthetic implant materials [12].…”
Section: Introductionmentioning
confidence: 99%